Factors influencing the formation of feeling of familiarity - Ευκλείδη Αναστασία; Πανταζή Μαρία; Γιαζκουλίδου Αικατερίνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF